Environmental correlates of the distribution of (E,E)-farnesol-rich Bothriochloa species (Poaceae) in South America - LIDIA R. SCRIVANTI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Scrivanti LR. 2026. Environmental correlates of the distribution of (E,E)-farnesol-rich Bothriochloa species (Poaceae) in South America. Biodiversitas 27 (3): d270302. https://doi.org/10.13057/biodiv/d270302. The genus Bothriochloa (Poaceae: Andropogoneae) comprises aromatic grasses, with several South American species reported to be rich in the oxygenated sesquiterpene (E,E)-farnesol. This compound exhibits significant pharmacological potential, including anti-obesity, antidiabetic, and anticancer activities. Despite its ecological and applied relevance, the environmental factors associated with the distribution of (E,E)-farnesol-rich Bothriochloa species remain poorly understood. This study evaluated the environmental correlates of the distribution patterns of ten South American Bothriochloa species characterized by high (E,E)-farnesol content, with the aim of identifying climatic and edaphic variables associated with their occurrence. Georeferenced occurrence records were compiled for ten Bothriochloa species and integrated with climatic and soil variables from the WorldClim and SoilGrids databases. Species distribution models (SDMs) were developed using Maxent to predict suitable habitats and to assess the relative contribution of environmental predictors. Model performance was evaluated using the area under the receiver operating characteristic curve (AUC), and variable importance was examined through permutation importance and jackknife tests. Most models showed high predictive performance, although some species were represented by a limited number of occurrence records, and predictions for these taxa should therefore be interpreted with caution. Climatic variables related to temperature stability, precipitation seasonality, and vapour pressure, together with edaphic factors such as soil pH and bulk density, consistently contributed to habitat suitability, although their relative importance varied among taxa. Suitable habitats were predicted across broad regions of South America, highlighting both widespread and geographically restricted distribution patterns among species. These results indicate that the distribution of (E,E)-farnesol-rich Bothriochloa species is associated with gradients of thermal constancy, moisture availability, and soil properties. Although the models do not directly address secondary metabolite production, they provide an ecological framework for understanding the environmental contexts in which these taxa occur, with potential implications for conservation planning, sustainable bioprospecting, and future ecological and phytochemical research on aromatic plants.